Aluminum and maganese tolerance on wheat (Triticum aestivum L.) cultivars - Brauner, J.L.; Sarruge, J.R. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
The influence of Al, Mn and differential tolerance to those elements in the P uptake were studied on excised roots of wheat seedlings by using Michaelis-Menten kinetics. The cultivars were Sonora 63C, Yecora and IAS 63, respectively, suscetible, intermediate and tolerant to Al; and CNTl, Sonora 63C and IAS 55, respectively, suscetible, inter mediate and tolerant to Mn. Labelled 32P solutions of CaCl2 ranged from 10-6M to 10-4 M. Solutions of AlCl3 and MnCl2 were 10-4M. The following conclusions reached: a) P uptake is realized through one mechanism; b) there are genetic differences in the P uptake, in the presence or absence of Al or Mn, without relations to tolerance of these elements; c) both Al and Mn increase P uptake but the Al stimulated more than Mn.